AI restoration brings 'dying' masterpieces back to life, but tricks copyright?. (24th November 2022) - Li, Yangzi
Abstract: Recently, artificial intelligence (AI) has shed light on the restoration of fragmentary masterpieces. It is said that AI-restored content can reproduce the missing part in fragmentary works, reveal authors' initial intention, and give the younger generation a chance to appreciate the essence of cultural heritage. AI restoration leads to a discussion on whether copyright law should apply to AI-restored works. The existing literature about the nexus between the restoration of works and copyright is scarce, and none is related to AI-restored works. Therefore, this paper focuses on investigating the potential copyright issues regarding AI-restored works and exploring how the traditional copyright regime fails to solve those issues. Besides, this paper suggests recalibrating the copyright regime to enhance the authenticity of AI-restored output. Lastly, this cutting-edge article provides theoretical evidence for IP scholars interested in AI-related issues and advocates future research on the relation between AI models and copyright law.